Liderazgo y Gestiòn comunitaria en el barrio Punzara Chico Bajo y la intervenciòn del Trabajador Social - Pineda Romero, Marìa del Cisne (2015)
The present work “Leadership and Community Administration in the neighborhood Punzara Chico Bajo and the Social Worker's Intervention” it arose starting from the preliminary poll that was carried out in this sector, where it was possible to determine “Weak Leadership and community administration” how the most outstanding social problem. Whereas clause that this also propitiates the origin of others that affect the quality of the residents' of the neighborhood life, is that the investigation is developed that will have as beneficiaries to the residents of the sector, by means of the application of alternatives that you/they allow to strengthen the leadership and community administration. The neighborhood Punzara Chico Bajo, scenario of the present investigation, it is located in the parish Punzara, to the Southwest of the city of Loja; it limits to the north: with the street Operadores; South: with the neighborhood Punzara Alto; East: Cdla. Esteban Godoy and West: Via inter-barrial. In spite of being an urban neighborhood, it doesn't have the basic services as: drinking water and sewer system; the condition of the roads is deplorable, the sport center and of recreation of the sector it constitutes it the school “Luis Humberto Benítez Costa”, because the neighborhood not to have another space for the communal coexistence. The objectives outlined for the development of the present investigation were; to strengthen the leadership and community administration to improve the quality of the residents' of the neighborhood life Punzara Chico Bajo of the city of Loja, through the theoretical and scientific foundation of the causes and goods of the weak leadership and community administration, conceptual explanation of the variables and indicators of the problem Object of Study and the position of an action proposal. 5 The first three stages of the Methodology of the Community Autodesarrollo were used: Stage 1: I exchange initial with the needy fellow of the professional action, Stage 2: Exploration of the scenario, Stage 3: Diagnosis and search of solutions. The techniques and utilized instruments were: reading and analysis of documents, observation and the applied interview to 90 residents of the neighborhood. The main results obtained with the interview were: at the moment the community doesn't have a leader, to motivate the residents to be organized and to carry out activities that offer social benefits; the sewer system services and illumination public, it is available only in the main road and not in alternating streets; who presides over the directive of the Meeting of the Water it points out that the main inconveniences that find the directing mires when assuming the position, are the scarce participation and the residents' of the sector cooperation, the residents apologize in front of this, explaining that they have lost the trust in you lead them because they had who they looked for to obtain personal benefits and they didn't worry about the necessities of the community; for the residents the quality of life in the neighborhood is to regulate, because they don't have services that helps them to maintain healthy conditions, and they constantly contract illnesses. Finally, its concludes that the residents of the neighborhood Punzara Chico Bajo, require to strengthen the leadership and community administration, by means of the promotion of community values, for what is recommended the execution of the action proposal about to reach this end.